Knowledge and Attitude Towards Human Papilloma Virus and Human Papilloma Virus Vaccine - Poudel, Sandesh; Rai, Snigdha; Adhikari, Shree Prasad; Dhakal, Sheela; Rai, Nisha; Upadhyaya, Preetam Chandra; Shah, Pushkal (Journal of Nepal Health Research Council, 2024)
Background: Human papilloma virus is the leading cause of cervical cancer with Human papilloma virus 16 and 18 being the commonest variants. The primary prevention by vaccination against HPV is finally gaining its momentum. This study aimed to evaluate the knowledge and attitude towards Human papilloma virus and Human papilloma virus vaccine and highlighted on the setback of their inadequate knowledge.Methods: This was a community based cross sectional study done among 120 women who attended cervical cancer screening camp at satellite clinic of Paropakar Maternity and Women`s Hospital at Bhaisepati of Kathmandu district. The interview was done one on one with a preformed questionnaire. Data was primarily entered in an individual form and analysis was done using SPSS version 23 program and was depicted in tables, diagrams and chart.Results: The mean age of the women was 41.8±9.9 with majority belonging to age group 41-50 years (47.16%), 88 (74%) women were multiparous,59 (49%) were uneducated and 50 (33%) were previously screened for cervical cancer. Among 27 (22%) of the women who had heard about HPV and knew that it causes cervical cancer, most of them have heard from social media while 110(91.6%) did not know about its vaccine and its availability while 100% of the participants had positive attitude towards receiving the information and keen on vaccinating their daughters.Conclusions: Knowledge and awareness of Human Papilloma Virus and its vaccine still remains low among the women in our society. However, there was high acceptance of HPV vaccine, indicating potentially high uptake rates in these communities. Keywords: Attitude; human papilloma virus; knowledge; vaccine.